DETERMINASI KEPUTUSAN PEMBELIAN TEH DITINJAU DARI KUALITAS PRODUK DAN CITRA MEREK (Universitas Muhammadiyah Palembang, 2023)
Purpose – Research to look at the determinants of tea purchasing decisions in terms of product quality and brand image, collectively and individually in the Keraton Kayu Agung sub-district. Design/methodology –This research is associative, as many as 100 samples were respondents, using purposive sampling as a sampling technique the analysis technique used in this research is multiple linear regression analysis Findings - The research results show that together there is an influence of product quality and brand image on the decision to purchase sariwangi tea in Kedaton Kayu Agung sub-district. Meanwhile, individually, there is an influence of product quality and brand image on the decision to purchase sariwangi tea in Kedaton Kayu Agung sub-district. Meanwhile, individually, there is an influence of product quality and brand image on the decision to purchase sariwangi tea in Kedaton Kayu Agung sub-district.